Two-dimensional periodic texture of actin filaments formed upon drying - Honda, Hajime (Biophysics (Nagoya-shi), 2011)
We found that a solution of actin filaments can form a periodic texture in the process of drying on a flat glass surface in the air; the periodic texture was composed of smooth meandering bundles of actin filaments. We also found that a branched salt crystal grows in the space between the meandering bundles of actin filaments. The distance between the adjacent striae (striation period) in the resulting dried two-dimensional pattern of striation decreased from about 50 to 2 μm, as the ambient temperature was increased from 4 to 40°C at 1 mg/ml actin, and showed an increasing tendency from a few to several tens μm with the increase in the initial concentration of actin filaments from 0.6 to 2.0mg/ml at room temperature. As the speed of drying is increased at a certain temperature, the striation period was also found to decrease. We propose that the formation of the two-dimensional striation pattern of bundles of actin filaments is the result of condensation of proteins due to dehydration, and suggest that the solvent flow from the center to the periphery of the sample causes the meandering of actin filaments.